EFFECT OF RESIDUAL LIGNIN AND HEXENURONIC ACIDS ON THE GENERATION OF ORGANOCHLORINES WITH CHLORINE DIOXIDE - Frigieri, Tania Cristina; Ventorim, Gustavo [UNESP]; Almeida Ferraz, Ana Paula [UNESP] (Editura Acad Romane, 2019)
The pulp and paper industry is one of the leading economic sectors that contribute to the contamination of the environment because of the use of organochlorine compounds, especially during the pulp bleaching process. For this reason, the objective of the present work was to analyze the organochlorines generated in the bleaching effluent (adsorbable organic halides, AOX). For this study, chips of Eucalyptus urograndis were subjected to the kraft cooking process. The thus-obtained brown pulp was divided into three samples: one remained unmodified, another was subjected to a treatment for removing lignin (TLR) and the third was treated to remove hexenuronic acids (THR). A pre-bleaching sequence (DE) was performed on the three pulp samples (brown, TLR and THR), for different kappa factors in order to determine the amount of AOX generated in the effluent. The results indicated that the lignin, when compared to the hexenuronic acids, generated a higher amount of AOX in the effluent.
Keywords: lignin; hexenuronic acids; AOX